Environment for the analysis and comparison of texture descriptors - Flórez Farfán, Alex Josué (2018)
Descargue el texto completo en el repositorio institucional de la Universidade de São Paulo: https://doi.org/10.11606/D.55.2019.tde-02012019-103709